Conservation Forensics : Decoding Historical Past of 135 - Year - Old Istana Warisan Datuk Pengiran Haji Matusin in Lawas, Sarawak - Yon Syafni, Samat; Mohd. Anis Yaziq, Alimin; Atta Idrawani, Zaini; Awang Hasim, Awang Sulong; Anis Farahin, Faisal; Megat Mohd Hilman Zamir, Zamri (UNIMAS RDICE, 2025)
The Istana Warisan in Kampung Dato’, Kuala Lawas, is the last remaining heritage structure in Lawas, Sarawak, believed to have been built in 1889 on the banks of Sungai Merapok. This historic building, originally owned by Pengiran Haji Matusin (1870-1952) bin Pengiran Abu Bakar - the fourth descendant of Sultan Umar Ali Saifudin 1 (1740-1795), showcases a typical Malay house typology usually found along the Sarawak River; an elevated wooden structure with a limas roof sitting on stone columns.